Pengaruh Kualitas Tidur yang Buruk Terhadap Kualitas Hidup Pasien Kanker - Jihan Salsabila Anggoro Putri; Fransisca Chondro (Universitas Ciputra Surabaya, 2023)
The quality of life of cancer patients can be affected by some important factors, and one of them is sleep quality. Cancer patients generally have a poor sleep quality and quality of life caused by sleep disorders experienced by the patience. The disorders can be the results or side effects of the course of the disease, the patient's therapy, and other specific factors related with certain types of cancer, such as respiratory symptoms in lung cancer patients. Usually, poorer sleep quality can be found in patients with severe symptoms. These can be the cause of a lower quality of life in cancer patients. Some studies found no significant relationship between sleep quality and quality of life in cancer patients. Thus, further research regarding relationship between sleep quality and quality of life in cancer patients is needed. The differences in the results can be influenced by various factors such as data collection time and use of different measurement instruments. Further investigation of factors and the mechanism of sleep quality disturbances in cancer patients also needed, in order to give a better care for the patients so the quality of life can be improved.